2021
DOI: 10.4103/ijo.ijo_1403_21
|View full text |Cite
|
Sign up to set email alerts
|

Does myopia decrease the risk of diabetic retinopathy in both type-1 and type-2 diabetes mellitus?

Abstract: Purpose: To study the relationship between the severity of myopia and the severity of diabetic retinopathy (DR) in individuals with type 1 or type 2 diabetes mellitus (DM). Methods: This retrospective study was conducted using data from electronic medical records from a multicentric eyecare network located in various geographic regions of India. Individuals with type 1 or type 2 DM were classified according to their refractive status. Severe nonproliferative DR (NPDR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Although there is overwhelming evidence to indicate that myopia has a protective effect against diabetic retinopathy, epidemiological studies show some inconsistencies [31][32][33][34][35]. Contrary to the huge evidence to support the protective effect of myopia against diabetic retinopathy, myopes in this study were found to be almost 11 times more likely at risk of DR (OR, 10.70; 95% CI, 3.91-29.27) compared to emmetropes and hyperopes (OR, 2.14; 95% CI, 0.70-6.53).…”
Section: Plos Onementioning
confidence: 99%
“…Although there is overwhelming evidence to indicate that myopia has a protective effect against diabetic retinopathy, epidemiological studies show some inconsistencies [31][32][33][34][35]. Contrary to the huge evidence to support the protective effect of myopia against diabetic retinopathy, myopes in this study were found to be almost 11 times more likely at risk of DR (OR, 10.70; 95% CI, 3.91-29.27) compared to emmetropes and hyperopes (OR, 2.14; 95% CI, 0.70-6.53).…”
Section: Plos Onementioning
confidence: 99%
“…We read an article entitled “Does myopia decrease the risk of diabetic retinopathy in both type-1 and type-2 diabetes mellitus?” by Thakur et al . [ 1 ] published in Indian Journal of Ophthalmology. The article evaluated the relationship between the severity of myopia and the severity of diabetic retinopathy (DR) in individuals with type-1 or type-2 diabetes mellitus (DM).…”
mentioning
confidence: 99%
“…We appreciate the comments and interest of the authors in our publication. [ 1 ] We would like to address the concerns raised in relation to our manuscript that aimed to investigate the relationship between the severity of myopia and the severity of diabetic retinopathy (DR) in individuals with type 1 and type 2 diabetes mellitus.…”
mentioning
confidence: 99%